Utility of Whole Exome Sequencing in the Early Diagnosis of Atypical Diamond-Blackfan Anemia. Issue 3 (9th April 2023) - Al-Mulla, Abdulla; Austin, Frances; Helou, Marieka
Abstract : Diamond-Blackfan anemia (DBA) is a rare congenital bone marrow failure syndrome, with a hallmark of erythroblastopenia and congenital anomalies. DBA demonstrates genetic heterogeneity and variable phenotypic expression. We present two cases of atypical DBA harboring de novo mutations in the RPS-19 gene with c.49 G>C and c.357-1G>T allelic variants. The two cases presented confounding critical illness demonstrated by multiorgan failure, aplastic crisis, with case 2 meeting the criteria for hemophagocytic lymphohistiocytosis. We highlight the utility of genetic testing in the early diagnosis of DBA and the associated complexities and burden of disease in caring for DBA patients.